Assessing the efficacy of natural soil biotin on soil quality, microbial diversity, and Rhododendron simsii growth for sustainable landscape architecture - Teng, Zhiyan; Chen, Lan; Li, Sheng; Pan, Kexuan; Liu, Dandan; Gu, Zaiyuan; Wang, Yijie; Huang, Li; Chen, Yunwen (Frontiers in Microbiology, 2024)
Fertilization significantly influences soil quality and its sustainable use in urban garden maintenance. The widespread application of inorganic fertilizers has raised ecological concerns due to their potential environmental impacts. Organic fertilizers, while beneficial, often have slow effects and are costly. Biofertilizers, with their eco-friendly nature and low carbon footprint, are gaining attention for their multifaceted role in supporting plant growth. Despite the focus on fruit trees, vegetables, and medicinal plants, ornamental plants have been understudied. This study aims to evaluate the efficacy of a novel microbial fertilizer, ‘natural soil biotin’, on Rhododendron plants, specifically the Azalea hybrid ‘Carnation’. The study employed a comparative approach to assess the impact of different fertilization strategies on soil properties, microbial diversity, enzyme activity, plant morphology, and physiological parameters. The application of ‘natural soil biotin’ was compared with the use of inorganic and organic fertilizers. The combined application of ‘natural soil biotin’ was found to effectively enhance soil properties and mitigate the impact of other fertilizers on soil pH. It also improved the relative abundance of beneficial microbial groups such as Proteobacteria, Ascomycota, and Basidiomycota. Furthermore, the mixed application significantly increased the activities of urease and sucrase in Rhododendron plants, which promoted their growth, development, and stress resistance. The results indicate that the mixed application of ‘natural soil biotin’ with inorganic and organic fertilizers not only improved the soil quality but also enhanced the efficiency of fertilizer utilization. This approach led to increased economic and environmental benefits in Rhododendron cultivation. The findings contribute to the foundation for soil improvement and ecological restoration, suggesting that ‘natural soil biotin’ could be a promising alternative or supplement to traditional fertilization methods in sustainable landscape architecture.